Investigação de métodos de predição de formação de hidratos na presença de inibidores - Alves, Daniel Bardini (2019)
Hydrates formation in oil extraction pipes Offshore is one of the biggest and recurrent challenges regarding flow assurance. The Oil Industry has great interest in understanding the phenomenon of hydrates formation, because they can damage oil production and transport lines, aside putting lives and the environment in danger. Gas hydrates are ice-like, crystalline molecular structures, which consists of water and low weight hydrocarbons, and its formation depends on temperature, pressure and the gas composition. In the past decades the number of scientific productions relating this issue had increased considerably, many complex mathematical models were developed to estimate when and where hydrates will form inside a pipeline. The purpose of this work is to inspect four calculation methods and compare them with data from literature. Taking as basis three commercial softwares (Multiflash, PVTSim e CSMGem) and a hydrate prediction routine in fortran90 using the van der Waals and Platteeuw theory and the state equation Cubic-Plus-Association (CPA). Pressure and temperature experimental data of hydrates formations were obtained from NIST’s data base for comparison with the results from each calculation method and then the error curves were made comparing each software’s results.